But was it murder? - Barrell, Jania (Cambridge English readers. Level 4, 2000)
Alex Forley had everything: good looks, money, a beautiful house in London, an attractive girlfriend and a close group pf friends. But now he is dead and Detective Inspector Rod Eliot wants the answers to two simple questions. Was it murder? And if so, who was the murderer?